Analisis Kebijakan Dividen dan Kebijakan Hutang Terhadap Nilai Perusahaan Go Publik di Indonesia - Rasyid HS Umrie; Yuliani Yuliani; Afriyadi Cahyadi (Program Studi Magister Manajemen FE Unsri, 2011)
The purpose of this study was to obtain empirical evidence about the effect of market growth, market risk , earnings volatility, profitability, capital of the company and firm size of policy dividends and policy leverage, examines the relationship between dividend policy and the policy leverage of value firms and empirically test the effect of dividend policy and the policy leverage of the firm value.The population of research are companies included in the manufacturing sectors. Sampling method was done by purposive sampling technique based on certain criteria. Retrieved 10 issuers that were taken as samples. Observation period 2006-2008. For the purposes of analysis used panel data during the observation. The data were analyzed using descriptive statistics and causality analysis of Structural Equation Modeling (SEM) operated by the software AMOS 6.0. The findings of this study, first, variables influencing the dividend policy is the volatility, equity and size. While the variable growth, beta and ROA was not affected. Second, the growth variable and the beta has no effect on the policy leverage. While the volatility variable, ROA, equity and size have an influence on policy leverage. Third, dividend policy has a significant relationship to the value of the company while the policy leverage has no significant relationship. Fourth, there interpendensi between dividend policy and the policy leverage of the firm value.Key Words : Dividend policy, Leverage and Value of the firm